2006
DOI: 10.1200/jco.2006.24.18_suppl.13117
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 study of daily oral perifosine (P) with weekly paclitaxel (T)

Abstract: 13117 Background: P is an oral signal transduction modulator with limited toxicity. P combined with 3-weekly T led to no toxicity beyond that expected with each drug alone. Weekly T is more effective than 3-weekly T in some settings (Seidman, ASCO 2004:512), so this study evaluated whether weekly T altered the tolerance to P. Methods: Twelve patients (pts) were enrolled. T was given at 80 mg/m2 on days 1, 8 and 15 of a 28 day cycle. P, 50 mg, was given 1, 2 or 3 times a day on days 1–21 of each cycle. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A phase I trial combining perifosine and radiotherapy in advanced solid tumors demonstrated that perifosine could be safely utilized as a radiation sensitizer, and phase II trials with this strategy are in development (Vink et al, 2006b). In addition, preliminary reports from a number of phase I trials investigating the combination of perifosine with traditional cytotoxic chemotherapeutic agents such as taxanes and gemcitabine indicate that these combinations can be safely administered (Cervera et al, 2006;Ebrahimi et al, 2006;Goggins et al, 2006;Weiss et al, 2006).…”
Section: Akt Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase I trial combining perifosine and radiotherapy in advanced solid tumors demonstrated that perifosine could be safely utilized as a radiation sensitizer, and phase II trials with this strategy are in development (Vink et al, 2006b). In addition, preliminary reports from a number of phase I trials investigating the combination of perifosine with traditional cytotoxic chemotherapeutic agents such as taxanes and gemcitabine indicate that these combinations can be safely administered (Cervera et al, 2006;Ebrahimi et al, 2006;Goggins et al, 2006;Weiss et al, 2006).…”
Section: Akt Inhibitorsmentioning
confidence: 99%
“…In trials combining mTOR inhibitors with conventional chemotherapy, unexpected toxicities in two trials lead to early discontinuation of the studies (Punt et al, 2003;Pacey et al, 2004). However, overlapping toxicities were not observed in preliminary data from trials combining perifosine with conventional chemotherapy (Cervera et al, 2006;Ebrahimi et al, 2006;Goggins et al, 2006;Weiss et al, 2006). Nevertheless, combining pathway inhibitors with conventional cytotoxic chemotherapy could result in more toxicity than when combining inhibitors with molecularly targeted agents.…”
Section: Toxicity Concernsmentioning
confidence: 99%
“…Furthermore, the maximum tolerated dose for the weekly perifosine was 1200 mg. In the second trial (NCT00431054)[ 173 ] the safety and efficacy of the combination of docetaxel and perifosine were studied on 22 patients with epithelial cancer of the ovary, fallopian tube cancer or gynecologic primary peritoneal cancer, which were platinum resistant or refractory. The third phase I trial (NCT00399126)[ 174 ] studied the gastrointestinal toxicity and cancer progression on the combination of daily perifosine with weekly or every 3-wk paclitaxel in 12 cancer patients.…”
Section: Pi3k/akt Inhibitors In the Clinicmentioning
confidence: 99%
“…A number of phase I trials have investigated the toxicity of combining the AKT inhibitor perifosine with traditional chemotherapeutic agents, such as docetaxel, paclitaxel, and gemcitabine [Cervera et al . 2006; Ebrahimi et al . 2006; Goggins et al .…”
Section: Opportunities and Challenges In Targeting Pi3k/akt In Colorementioning
confidence: 99%